2018
DOI: 10.3389/fphar.2018.00626
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Nicotinic Acetylcholine Receptors Support Liver Cells Viability After Partial Hepatectomy

Abstract: Nicotinic acetylcholine receptors (nAChRs) expressed on the cell plasma membrane are ligand-gated ion channels mediating fast synaptic transmission, regulating neurotransmitter and cytokine release and supporting the viability of many cell types. The nAChRs expressed in mitochondria regulate the release of pro-apoptotic factors, like cytochrome c, in ion channel-independent manner. Here we show that α3β2, α7β2, and α9α10 nAChR subtypes are up-regulated in rat liver mitochondria 3–6 h after partial hepatectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 56 publications
5
18
0
Order By: Relevance
“…Interestingly, localization to the mitochondria (GO:0005739, FDR 0.0004) was also enriched, agreeing with previous studies that identified α 7-nAChR function in the mitochondrial membrane. 36 Proteins localized in neuron projections (GO:0043005, FDR 0.008), including α 7 subunits, were also enriched, which is consistent with the observation that development of neuron projections (i.e., neurites) is mediated by α 7-nAChRs (Figure 5, Figure 7). 37…”
Section: Resultssupporting
confidence: 84%
“…Interestingly, localization to the mitochondria (GO:0005739, FDR 0.0004) was also enriched, agreeing with previous studies that identified α 7-nAChR function in the mitochondrial membrane. 36 Proteins localized in neuron projections (GO:0043005, FDR 0.008), including α 7 subunits, were also enriched, which is consistent with the observation that development of neuron projections (i.e., neurites) is mediated by α 7-nAChRs (Figure 5, Figure 7). 37…”
Section: Resultssupporting
confidence: 84%
“…Several components of CSE may influence different steps in mito-ncR-805 regulation. Nicotine has pro-survival effects, with cell-type-specific responses that depend on the repertoire of nicotinic acetylcholine receptors (nAChRs) on the cell surface and on the mitochondrial membrane itself in the given cell type 59 61 . We do not know whether a single component of CSE is responsible for all spatial–temporal changes in mito-ncR-805, or the response is a complex reaction that culminates from the effects of several CS components, or is a result of a signaling event through nAChRs or other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of both PNU282 and PNU120 to influence the nAChR content in the brain of LPS-injected mice demonstrated two important things: the ''plasticity'' of the brain nAChRs and the potency of α7 nAChRs in influencing the expression of other nAChR subtypes in the brain. We have already reported up-regulation of α3β4 and α9β4 nAChRs in the mitochondria of α7−/− mice (Arias et al, 2018;Uspenska et al, 2018b) and up-regulation of α3β4 nAChRs in LPS-treated mice where α7 and α4β2 nAChRs were down-regulated (Lykhmus et al, 2015a(Lykhmus et al, , 2019a. Therefore, the deficiency of cognitively important α7 and α4β2 nAChRs was accompanied by up-regulation of α3β4 and α9β4 nAChRs that neither compensated memory decline nor supported mitochondria stability.…”
Section: Discussionmentioning
confidence: 94%
“…A separate line of evidence demonstrates that α7-containing nAChRs are expressed in the outer membrane of mitochondria and regulate the early events of mitochondria-driven apoptosis, such as cytochrome c release (reviewed in . The initial finding (Gergalova et al, 2012) was further supported by the data showing the involvement of mitochondrial nAChRs in liver regeneration (Uspenska et al, 2018b) and in neuroinflammation (Lykhmus et al, 2015a). In contrast to the nAChRs expressed in the plasma membrane, those exposed to the intracellular environment do not function as ion channels but influence intramitochondrial kinases in an ion-independent manner (Gergalova et al, 2014).…”
Section: Introductionmentioning
confidence: 86%